Systemic JIA-Associated Lung Disease: A Multicenter Analysis of Clinical Features, Treatment Challenges, and Outcomes - Unal, Dilara; Cam, Veysel; Konte, Elif Kilic; Celikel, Elif; Ozdel, Semanur; Gurgoze, Metin Kaya; Ozen, Seza (Wiley, 2026)
Background: Systemic juvenile idiopathic arthritis (sJIA) (Still's disease) associated lung disease (sJIA-LD) is a rare but severe complication, characterized by pulmonary involvement with high morbidity and mortality rates. While the incidence of sJIA-LD has increased, its pathogenesis and risk factors remain poorly understood. Objectives: This multicenter retrospective study aimed to evaluate the clinical, radiological, and laboratory features of patients with sJIA-LD, assess the impact of prior biologic treatments, and analyze treatment outcomes. Methods: Data were collected from 18 patients diagnosed with sJIA-LD between 2007 and 2024 across five pediatric rheumatology clinics in our country. Clinical features, imaging findings, and treatment regimens before and after sJIA-LD diagnosis were analyzed. HLA-DRB1*15 typing was performed in a subset of patients. Results: The median age of sJIA-LD diagnosis was 11.21 years, with a median disease duration of 2.76 years from sJIA diagnosis. Macrophage activation syndrome (MAS) occurred in 88.9% of patients prior to the diagnosis of lung disease. Cough (100%), dyspnea (83.3%), and clubbing (50%) were the most common clinical manifestations. Ground-glass opacities were the most frequent imaging finding (61.1%). DRESS was observed in 11.1% of patients, with 27.7% experiencing adverse reactions to biologics. Treatment revision after sJIA-LD diagnosis occurred in 83.3% of patients, with JAK inhibitors demonstrating clinical improvement in some cases. The overall survival rate was 94.4%, with one death due to fulminant MAS. Conclusion: This study provides data from a geographically underreported population in Turkey and the Eastern Mediterranean region. In our cohort, treatment modification after sJIA-LD diagnosis was common, while biologic therapy was often continued. These findings highlight the heterogeneous course of sJIA-LD. Further prospective multicenter studies are needed to optimize treatment strategies and improve risk stratification.
Keywords: Lung Disease; Macrophage Activation Syndrome; Still'S Disease